2020
DOI: 10.1111/1365-2664.13661
|View full text |Cite
|
Sign up to set email alerts
|

Plant traits, biotopes and urbanization dynamics explain the survival of endangered urban plant populations

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…Although these species occurred only in one or two gardens and their populations were small, it demonstrates the potential of urban gardens as a space for rare and endangered species of agricultural and rural areas. While population survival of endangered plant species is challenging in many urban habitats, greenspaces in Berlin have been shown to harbor established populations of some endangered species of ruderal areas (Planchuelo et al 2020). In community gardens, these plants could also benefit from organic cultivation and avoidance of herbicides, which was also documented in studies of organic and conventionally managed fields (Gabriel et al 2006;Salonen et al 2011;Rydberg and Milberg 2012;Albrecht et al 2016).…”
Section: High Diversity Of Cultivated and Wild Growing Plant Species ...mentioning
confidence: 95%
“…Although these species occurred only in one or two gardens and their populations were small, it demonstrates the potential of urban gardens as a space for rare and endangered species of agricultural and rural areas. While population survival of endangered plant species is challenging in many urban habitats, greenspaces in Berlin have been shown to harbor established populations of some endangered species of ruderal areas (Planchuelo et al 2020). In community gardens, these plants could also benefit from organic cultivation and avoidance of herbicides, which was also documented in studies of organic and conventionally managed fields (Gabriel et al 2006;Salonen et al 2011;Rydberg and Milberg 2012;Albrecht et al 2016).…”
Section: High Diversity Of Cultivated and Wild Growing Plant Species ...mentioning
confidence: 95%
“…A study by Planchuelo et al (2020) on the impact of urbanization dynamics on endangered plant species in Berlin also showed that 36% of endangered plant species were locally extinct within 10 years with increase of PTIA. In contrast, the results of this study showed that PTIA had a positive impact on the overall plant diversity of all scale URHs in the range of 100-1600 m. In addition, the effects of PTIA on plant diversity at different levels of URH of different sizes were signi cantly different in the range of 100-1700m (for example, tree diversity of large and medium-sized URHs was negatively correlated with PTIA, while shrub diversity was positively correlated).…”
Section: Ptia and Plant Diversity At Various Levels Of Urhmentioning
confidence: 98%
“…It might be the time-delay effects of fragmentation on plant diversity in the remnant habitats. Generally, remnant habitats with larger areas, better landscape connectivity, and long-lived species, might need a longer time to response to fragmentation, while those with smaller areas might have a quick response in shouter time to fragmentation (Planchuelo, et al, 2020). The rapid development of urbanization in Guiyang began almost 30 years ago, so it is not clear to what extent and spatial scale the overall plant diversity of large and medium-sized URHs would be affected by fragmentation.…”
Section: Fi and Plant Diversity At Different Levels Of Urhsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different urban drivers contribute to plant traits selection (Williams et al 2009, 2015) and challenge plant recruitment (Piana et al 2019). For example, habitat transformation and fragmentation as well as novel urban ecosystems modulate the establishment and long‐term survival of plant species (Kowarik and von der Lippe 2018, Planchuelo et al 2020). Furthermore, fragmentation of urban environments can lead to a loss of species that require large habitats (Beninde et al 2015).…”
Section: Introductionmentioning
confidence: 99%